PENGARUH KREATIFITAS BERCERITA GURU SEKOLAH MINGGU TERHADAP MINAT ANAK BERIBADAH DI GBI PETAMBURAN - Sumarno, Yuel; Catharine Rachel Marlissa (Edukasi : Jurnal Pendidikan Agama Kristen, 2020)
Children's interest in Sunday School worship is a spirit that must be internalized in all things. Many factors cause children to want to come to worship. Starting from a good room, lots of props, and teacher creativity. One influence that needs special attention is the teacher's way of telling stories in teaching. This article analyzes the influence of Sunday School teachers' creativity in telling stories on children's interest in worshiping at Indonesian Bethel Children aged 8-12 years. The research method used is quantitative, with a data collection model through surveys. The hypothesis is that there is an influence between the creativity of Sunday School teachers in telling stories on the interest of ABI children aged 8-12 years at GBI Petamburan. So from the hypothesis testing analysis, it was concluded that there was a low influence between the creativity of Sunday school teachers in telling stories on the interest of ABI children aged 8-12 years in worship at GBI Petamburan with a strong relationship between this variable of 0.251. Moreover, the contribution to children's interest in worship is only 6.3%, and the remaining 93.7% is determined by other variables that were not used as variables in this research. Thus, the influence of Sunday school teachers' creativity in telling stories on the interest of ABI children aged 8-12 years at GBI Petamburan is low.